2011
DOI: 10.1007/s00018-011-0805-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental nicotine exposure induced alterations in behavior and glutamate receptor function in hippocampus

Abstract: In the developing brain, nicotinic acetylcholine receptors (nAChRs) are involved in cell survival, targeting, formation of neural and sensory circuits, and development and maturation of other neurotransmitter systems. This regulatory role is disrupted when the developing brain is exposed to nicotine, which occurs with tobacco use during pregnancy. Prenatal nicotine exposure has been shown to be a strong risk factor for memory deficits and other behavioral aberrations in the offspring. The molecular mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 80 publications
(92 reference statements)
1
51
0
Order By: Relevance
“…More recently, we showed a substantial upregulation of subunits of NMDA and AMPA receptors and other proteins important for synaptic plasticity in newborn P1 rat pups [14]. In young adults, muted tissue levels of glutamatergic receptor subunits, accompanied with downregulated 3 [H] AMPA binding of functional AMPARs in the hippocampus [14] is consistent with a reduction in LTP induction in gestational nicotine treated animals [15]. The reduction in LTP induction is attributable to reduced amplitude and frequency of AMPAR-mediated EPSCs after nicotine treatment [15], [16].…”
Section: Introductionmentioning
confidence: 52%
“…More recently, we showed a substantial upregulation of subunits of NMDA and AMPA receptors and other proteins important for synaptic plasticity in newborn P1 rat pups [14]. In young adults, muted tissue levels of glutamatergic receptor subunits, accompanied with downregulated 3 [H] AMPA binding of functional AMPARs in the hippocampus [14] is consistent with a reduction in LTP induction in gestational nicotine treated animals [15]. The reduction in LTP induction is attributable to reduced amplitude and frequency of AMPAR-mediated EPSCs after nicotine treatment [15], [16].…”
Section: Introductionmentioning
confidence: 52%
“…In the present study, BPA exposure in whole juvenile phase just has effect on the memory consolidation. It implies that the hippocampus in juvenile animals is less sensitive to BPA exposure than it in the first developmental stage, which is characterized with large amounts of mature synapses (a form of synaptic plasticity) until postnatal 21 d (end of lactation)11 and vulnerable to many chemical exposure, including nicotine, Pb, and polybrominated diphenyl ethers 21. However, BPA exposure from gestation to juvenile will have progressively worse effect on memory than perinatal exposure only.…”
Section: Discussionmentioning
confidence: 99%
“…Methods have included maternally implanted osmotic minipumps (Eppolito et al 2010;Parameshwaran et al 2012), direct nicotine injection to pups (MacPhail et al 2007), or gavage to mother or pups (Lesage et al 2006;Mitchell et al 2012). These studies have shown that offspring express increased anxiety (Eppolito et al 2010), changes in acoustic startle response (ASR) and open-field locomotor activity (Gaworski et al 2004;MacPhail et al 2007), greater immobility time in the forced swim test (Parameshwaran et al 2012), and other effects. However, another study found no effects on open-field, ASR, or passive avoidance when each was tested at different ages (Gaworski et al 2004).…”
Section: Introductionmentioning
confidence: 99%